Septin-Dependent Assembly of a Cell Cycle-Regulatory Module in Saccharomyces cerevisiae - Longtine, Mark S. (American Society for Microbiology, 2000)
Saccharomyces cerevisiae septin mutants have pleiotropic defects, which include the formation of abnormally elongated buds. This bud morphology results at least in part from a cell cycle delay imposed by the Cdc28p-inhibitory kinase Swe1p. Mutations in three other genes (GIN4, encoding a kinase related to the Schizosaccharomyces pombe mitotic inducer Nim1p; CLA4, encoding a p21-activated kinase; and NAP1, encoding a Clb2p-interacting protein) also produce perturbations of septin organization associated with an Swe1p-dependent cell cycle delay. The effects of gin4, cla4, and nap1 mutations are additive, indicating that these proteins promote normal septin organization through pathways that are at least partially independent. In contrast, mutations affecting the other two Nim1p-related kinases in S. cerevisiae, Hsl1p and Kcc4p, produce no detectable effect on septin organization. However, deletion of HSL1, but not of KCC4, did produce a cell cycle delay under some conditions; this delay appears to reflect a direct role of Hsl1p in the regulation of Swe1p. As shown previously, Swe1p plays a central role in the morphogenesis checkpoint that delays the cell cycle in response to defects in bud formation. Swe1p is localized to the nucleus and to the daughter side of the mother bud neck prior to its degradation in G(2)/M phase. Both the neck localization of Swe1p and its degradation require Hsl1p and its binding partner Hsl7p, both of which colocalize with Swe1p at the daughter side of the neck. This localization is lost in mutants with perturbed septin organization, suggesting that the release of Hsl1p and Hsl7p from the neck may reduce their ability to inactivate Swe1p and thus contribute to the G(2) delay observed in such mutants. In contrast, treatments that perturb actin organization have little effect on Hsl1p and Hsl7p localization, suggesting that such treatments must stabilize Swe1p by another mechanism. The apparent dependence of Swe1p degradation on localization of the Hsl1p-Hsl7p-Swe1p module to a site that exists only in budded cells may constitute a mechanism for deactivating the morphogenesis checkpoint when it is no longer needed (i.e., after a bud has formed).